2020
DOI: 10.1016/j.vetmic.2020.108804
|View full text |Cite
|
Sign up to set email alerts
|

β-cantenin is potentially involved in the regulation of c-Jun signaling following bovine herpesvirus 1 infection

Abstract: Highlights BoHV-1 infection promotes nucleus accumulation of p-c-Jun(S73) and p-β-catenin(S552) The association between β-catenin and c-Jun in in nucleus is readily detected following BoHV-1 infection. BoHV-1 infection stimulates the expression and activation of c-Jun potentially through β-catenin. BoHV-1 infection leads to relocalization of nucleus c-Jun to form specific foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…β-catenin signaling is essential for cell survival [ 47 ]. iCRT14 at a concentration of 10 μM did not show cytotoxicity to MDBK cells in the absence of virus infection as we described elsewhere [ 48 ]. Here, we found that apoptotic bodies are readily detected in virus-infected cells in the presence of iCRT14 ( Figure 5 , numbered 1 to 3), suggesting that apoptosis is induced in virus-infected cells by iCRT14.…”
Section: Resultsmentioning
confidence: 74%
“…β-catenin signaling is essential for cell survival [ 47 ]. iCRT14 at a concentration of 10 μM did not show cytotoxicity to MDBK cells in the absence of virus infection as we described elsewhere [ 48 ]. Here, we found that apoptotic bodies are readily detected in virus-infected cells in the presence of iCRT14 ( Figure 5 , numbered 1 to 3), suggesting that apoptosis is induced in virus-infected cells by iCRT14.…”
Section: Resultsmentioning
confidence: 74%